TEACHERS’ SELF-EFFICACY IN HANDLING AGGRESSIVE BEHAVIOUR AMONG KINDERGARTEN CHILDREN - Lee, J.C.; Shminan, A.S.; Rehman Ullah, Khan; Voon, Siok Ping
Aggressive behaviour among kindergarten children is not something new in the world of education. Whether they like it or not, kindergarten teachers have to accept the fact that it is part of their job to face as well as to handle aggressive behaviour among children in kindergarten. Even though most of the inservice kindergarten teachers are trained, scant attention has been paid to their self-efficacy as well as its sources in terms of handling aggressive children, especially in Malaysian setting. The objective of this study was to identify the level and sources of kindergarten teachers’ self-efficacy in handling aggressive behaviour among children in kindergarten. Using the simple random sampling technique, responses to sense of self-efficacy and its sources of influence when handling aggressive behaviour among children in kindergarten were sought from 768 in-service kindergarten teachers across Malaysia via e-mail. Based on the finding of this study, Emotional Self-efficacy has the highest overall mean followed by Cognitive Self-efficacy and Behavioural Self-efficacy. In terms of sources of influence on kindergarten teachers self-efficacy, Mastery Experience contributed the highest effect followed by Verbal Persuasion and considered as prominent predictors. Thus, it is suggested that in-house training for in-service kindergarten teachers explicitly address these sources of self-efficacy. With better training opportunity and continuous professional development for in-service kindergarten teachers regarding their self-efficacy (Emotional, Cognitive, and Behavioural) in handling aggressive behaviour among children in kindergarten, it will be a win-win situation for both the teachers as well as the children.